Staropolskie ciało, jakie było, każdy przeczyta - Obremski, Krzysztof (Przestrzenie Teorii, 2013)
The 9th issue of the magazine published by the Faculty of Languages, Nicolaus Copernicus University, i.e. “Litteraria Copernicana” is the subject of this review. The issue is entitled “The body in early modern Polish literature”. The informative value of this magazine mostly lies in the fact that early modern Polish literature has begun to be read in a manner that is characteristic of the contemporary humanities which are concerned with this peculiar topic of studies, i.e. the body.